Lei simbólica, desamparo e pânico na contemporaneidade: um estudo psicanalítico - Costa, Veridiana Alves de Sousa Ferreira (2005)
The current context presents changes in the subjectives organization ways. Inside this, the redefinitions from the man and woman roles, the new filiation forms, as the new familiar configurations, have brought to a references crisis that reaches different sections from the human life. Among others aspects, this has been implied on redimensionment of the father s place, traditionally conceived as representing from the symbolic law. The father social role is so questioned and, many times, confused with the decline from the paternal function, but, is there is a decline, it is from the patriarchal power, and not of its function, that stays as structural. Fundamental to the structuring of human being and to the social coexistence, the law presents itself like a way of symbolic support. In front of this, we question how stays the reference from the symbolic law, that in the current panorama, it seems leave important blanks in its duties. Inefficient in the limit and interdiction function, the law fails, as well the advantages that should assure of her. No more interdicted, the subject sees himself summoned to the excess and, paradoxally, without references, unsupported. The human condition of unssuporting constituent of the subject due to the life circumstances of people have been exacerbated, what reveals a constant unssuporting situation in which live the nowadays subjects. This leave them to new psychic disorganization forms and makes emerge new symptomatologic configurations, in which expression forms are linked to specific contexts. Among them, the panic disorder highlights as a illustration of the unssuporting more often evocated in the contemporary times, due to the fragility which the law presents itself